Regional‐scale development of opening‐mode calcite veins due to silica diagenesis. (13th July 2017) - Hooker, John N.; Huggett, Jennifer M.; Cartwright, Joe; Ali Hussein, Mohammad
Abstract: The formation and distribution of natural fractures in Cretaceous‐Paleogene strata in Jordan are strongly tied to diagenetic processes, which in turn reflect the lithology of the host material. Observations collected from subsurface cores show that widespread fracturing began before compaction of the host sediment was complete, based on ptygmatic folding of one set of mineral‐filled fractures (veins). Nonfolded veins are preferentially developed within heavily cemented layers. Calcium carbonate is the greatest volumetric component of the host sediment, and most fractures are at least partially filled by calcite. Dolomite‐bearing and silica‐bearing fractures are present in dolomitized and silicified host beds, respectively. Horizontal veins are filled by cone‐in‐cone calcite or, rarely, silica or dolomite. The stratigraphic arrangement and degree of compaction around ptygmatically folded calcite veins and chert nodules suggest that silica diagenesis was an important driver of early fractures. Nevertheless, those fractures were filled with carbonate cements as they opened, based on crack‐seal texture of the vein fill. The volume loss associated with silica diagenesis created fracture porosity, which was filled coevally by carbonate cements. The distribution of later veins reflects embrittlement of host layers by cementation and is consistent with crustal deformation as the primary fracture driver. Plain Language Summary: This paper describes natural fractures in mudrocks from Jordan. We present various lines of evidence that the fractures formed in response to volume loss associated with the transformation of opal into quartz (i.e., silica diagenesis) during early burial. Interestingly, these fractures also filled with calcite while they opened. Calcite is not directly involved in silica diagenesis. Therefore, this paper presents new evidence that chemical reactions can open fracture pore space in rocks, and that that space can be filled by another material. This sequence implies that the permeability of the host material can be affected by the development of chemically induced fractures. Key Points: Fractures in the Cretaceous‐Paleogene of Jordan formed in response to volume loss during silica diagenesis Nevertheless, early fractures filled with carbonate cements as they formed Volume‐reducing diagenetic reactions can therefore create fracture porosity, which can be filled by unrelated material